Taxonomic notes on the leafwing butterflies Memphis leonida (Stoll) and Memphis editha (Comstock), stat. nov. (Lepidoptera: Nymphalidae: Charaxinae) - Dias, Fernando Maia Silva; Casagrande, Mirna Martins; Mielke, Olaf Hermann Hendrik (Zootaxa, 2012)
The taxonomy of Memphis leonida (Stoll) is revised and an assessment of the names currently considered synonyms or subspe-cies are presented. Lectotypes of Papilio leonida Stoll and Paphia porphyrio Bates are designated, and one new status is pro-posed for Memphis editha (Comstock), stat. nov., a species currently regarded as a subspecies of M. leonida. Genitalic andwing shape and pattern characters suggest that M. leonida, occurring in the Amazon basin and the Guyanas, and M. editha,occurring in the Atlantic rain forest, are distinct species. Redescriptions, taxonomic notes, illustrations of male and female genitalia, and up-to-date distribution maps for the taxa are given.